Cooperative Behaviors in Group-Living Spider Mites - Schausberger, Peter; Yano, Shuichi; Sato, Yukie (Frontiers in Ecology and Evolution, 2021)
Cooperative behaviors are evolutionary stable if the direct and/or indirect fitness benefits exceed the costs of helping. Here we discuss cooperation and akin (cooperation-like) behaviors in sub-social group-living species of two genera of herbivorous spider mites (Tetranychidae), i.e. the largely polyphagous Tetranychus sp. and the nest-building Stigmaeopsis sp., which are specialized on grasses such as bamboo. These spider mites are distributed in patches at various spatial scales, that is, within and among leaves of individual host plants and among individual hosts of single or multiple plant species. Group-living by spider mites is brought about by plant-colonizing foundresses ovipositing at local feeding sites and natal site fidelity but also by multiple individuals aggregating in the same site in response to direct and/or indirect cues, many of which are associated with webbing. In the former case the emerging patches are often composed of genetically closely related individuals while in the latter case local patches may consist of kin of various degrees and/or non-kin and even heterospecific spider mites. We describe and discuss ultimate and proximate aspects of cooperation by spider mites in host plant colonization and exploitation, dispersal, anti-predator behavior and nesting-associated behaviors and conclude with theoretical and practical considerations of promising future research on cooperation in these highly rewarding model animals.